Chapter IV: the visit to Universitas Tanjung Pura & educational buildings / Janet Victoria Stia and Valerie Michael - Stia, Janet Victoria; Michael, Valerie (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Three lecturers from UiTM Cawangan Sarawak and one from Universitas Tanjungpura were given the opportunity to give public lectures on their specialised topics. Dr. Asmah Alia Mohamad Bohari, gave a talk on Green Procurement for the Malaysian Construction Industry, Mr. Mohamad Hafiz Hassan gave a talk on Visual Spatial: Building Design for Children with Autism Spectrum Disorder. On the other hand, Ms. Atiqah Husaini gave insight into Preserving the Malay House in the Sarawak Context. Lastly, Ms. Lestari from Universitas Tanjungpura shared her thoughts on The Future of Wood Construction.